Differences in College Readiness Rates in Two School Years for Students in Special Education (Global Journal of Human-Social Science, 2017)
Examined in this study were the college readiness rates i e reading mathematics and both subjects of students who received special education services in the 2012-2013 and 2013-2014 school years Data from the 2012-2013 and 2013-2014 Texas Academic Progress Reports were obtained and analyzed Students who received special education services had a statistically significantly higher reading college readiness rate in the 2013-2014 school year than in the 2012-2013 school year Mathematics college readiness rates were statistically significantly lower in the 2013-2014 school year than the 2012-2013 school year The college readiness rates for both subjects approached statistical significance and college readiness rates were lower in the 2013-2014 school year Of importance were the very very low college readiness rates of students who were enrolled in special education Implications of these findings and recommendations for future research are discussed
Keywords: college readiness; reading; mathematics; both subjects; special education